Emotional skills in medical residency selection interviews (Research, Society and Development, 2025)
The selection process for medical residency programs in Brazil has increasingly incorporated, in addition to the assessment of technical competencies, the recognition of the importance of emotional skills such as empathy, resilience, and emotional intelligence. This study aimed to analyze the presence, characteristics, and evaluation criteria of the interview stage in Brazilian medical residency selection processes, identifying which competencies are valued, the degree of standardization among public calls, and how these elements reflect contemporary demands in medical training, particularly with regard to the assessment of soft skills. The variables were analyzed through descriptive statistics and qualitative categorization based on Bardin’s content analysis. It was observed that 52% of the calls included an interview as an evaluative component, although 7.7% of them did not specify the criteria used. The score assigned to the interview ranged from 2 to 50 points, with a predominance of weight between 10% and 20% of the final grade. The most valued socioemotional competencies included empathy, ethics, emotional intelligence, leadership, and teamwork. Despite the growing emphasis on soft skills, the lack of standardization in criteria and scoring reveals weaknesses in the process. It is concluded that the interview has become an important stage in the selection process; however, it still lacks clear guidelines to ensure fairness and effectiveness in evaluation. The study suggests the creation of standardized criteria and the strengthening of medical education in emotional competencies, aiming to select and train professionals better prepared for the human and technical challenges of medical practice.